2. Supervisi Bersama Dengan Teknik Lomba Penilaian Administrasi Meningkatkan Kualitas Madrasah Ibtidaiyah Binaan Kecamatan Tanah merah Bangkalan - Usman, M. (PGSD Universitas WR Supratman Surabaya, 2017)
Supervisory Madrasah is functional official who serves as technical executor in carrying out surveillance of Education with the main task to assess and foster education at a Madrasah, given both public and private that is its responsibility, as stipulated in the decree Mendiknas number 020 / U / 1998 and SK Menpan number 091 / Kep / M.PAN / 10/2001 and SK Mendiknas number 097 / U / 2002.                In performing its duties Madrasah Supervisors have the authority to select and define working methods in order to achieve optimum results in accordance with the code of professional conduct. Regulation of the Minister of National Education of the Republic of Indonesia No. 19 of 2007 on the management standards by educational units include 1. Planning program. 2. Implementation of the work plan. 3. Monitoring and evaluation. 4. Leadership Madrasah / madrasah. 5. The management information system. 6. Special Rate.                The term supervision comes from two words,